Development of a Restructured Sweet Potato French Fries Type Product - Utomo, Joko Susilo (2009)
The 17 accessions from UPM collection and 4 commercial cultivars exhibited wide variation in physical and chemical characteristics. Results found that white flesh colour sweet potato showed the lowest hardness and followed by orange, yellow and purple cultivars. Starch content of 17 accessions varied significantly and amylose content of purple group was higher than the others. Yellow flesh group contains the highest fructose followed by orange, white and purple. Gelatinization temperatures for white, yellow, orange and purple were 78, 77, 73, and 72 °C, while the peak viscosity varied from 443 to 621, 510 to 725, 380 to 419 and 691 to 711 BU, respectively. The 17 accessions and 4 cultivars of sweet potato studied exhibit great variation in physical and chemical characteristics. On the optimizing method for RSS processing, White cultivars was chosen as raw material, and processed using the combination of shapes, blanching methods and adding of sweet potato flour. Results showed that chips exhibited a proper shape for blanching compared with dice. Blanching in 1 % STP solution for 2 minutes significantly improved the quality of RSS such as firmness and dry matter content of dough, colour, fat and ash content, and texture. Mixing of 5 % sweet potato flour to the mashed sweet potato produced suitable conditions of the dough for further processing and generated RSS having uniform shape with an intermediate hardness, high lightness and low redness colouration and also the highest value of sensory preferences. Sweet potato cultivars significantly affected the chemical, physical properties and organoleptic characteristics of RSS. Moisture content of Orange fresh tuber was lower than White and Yellow cultivars, and it generated the lowest moisture content of mashed sweet potato, prefried sticks and fried sticks. White cultivar generated the RSS having yellow bright colour, highest value of firmness and low fat content, while Orange cultivar produced RSS with bright orange colour, medium firmness but high fat content. RSS made of both varieties were evaluated as acceptable by a sensory panel with sensory score above the average. Recommendation from this study illustrates that White and Orange cultivars can be used to make a convenient restructured product. On the final preparation of RSS, deep frying and heating in microwave oven was evaluated on the texture attributes and sensory preferences of the product. Results showed that the most suitable condition of producing RSS was by using deep frying for final preparation on RSS made from White and Orange commercial cultivars as raw material. RSS made from White cultivar had hard texture, bright yellow colour and slightly below like slightly, while Orange RSS had softer texture, bright orange colour and slight above like slightly. Deep frying is the preferred method for the final preparation of RSS. From these findings, one may recommend that RSS can be produced using White and Orange cultivars. The tubers are peeled, sliced into about 2.3 mm thickness and 25 mm width. Blanching was done by dipping the chip in 1 % (w/v) STP solution at about 100 °C for 2 minutes. The blanched materials were drained for about 3 minutes to remove excess water, and then mashed and CMC was added (0.3 %, w/w) as a binder. The mashed was mixed with 5 % sweet potato flour. Moulding could be done using simple extruder with 10 x 10 mm square holes. The sticks were then deep fried at 163 °C for 1 minute, packaged in plastic bags and frozen at -20 °C for storage purpose until final preparation. The RSS was prepared by deep frying in 175 °C for 2 minutes.